(untitled) (RECIIS, 2011)
Obra ResenhadaBARGHINI, Alessandro. Antes que os Vaga-Lumes Desapareçam ou Influência da Iluminação Artificial sobre o Ambiente. São Paulo, Editora ANNABLUME; FAPESP, 2010. 192 p. ISBN:978-85-391-0057-6.